Several Aspects of the Economic Motivation for the Charity Activity (the Example of the Yekaterinburg Enterprises) - ВандышевМихаил Николаевич; ПетроваЛариса Евгеньевна (Journal of Economic Sociology, 2010)
Almost all enterprises have charity activity in that or this form. At the same time the question of why they are doing so is not clear: help giving is a rational action but its economic effects are not so clear. The paper provides some results of the sociological investigation of the charity activity of the business, which was conducted by the international consulting centre (Yekaterinburg) in 2002-2003 within the project “Business-sector and non-commercial organizations on the Middle Urals: the start for the collaboration and the partner perspectives”.